"Tech-to-Stretch": Expanding Possibilities for Literature Response - Whitin, Phyllis E. (The Reading teacher, 2009)
This article explores one context in which language arts instruction can be enhanced through digital technologies. It describes how preservice elementary education teachers first investigated aspects of visual literacy and then engaged in digital and traditional multimodal forms of response to historical nonfiction literature. They read, interpreted images, posted online written and visual responses, created symbolic collages, role played, enacted dramatic tableaux, and conversed. Next, they selected from and redesigned these varied representational resources to create collaborative digital movies in which they further explored an aspect of the book. Three of the group projects are analyzed for the ways in which the students capitalized upon the particular affordances of the various modalities. Implications for elementary and middle school classroom instruction are described. تستكشف هذه المقالة سياقاً تستطيع فيه التقنيات الرقمية أن تحسن تعليم الفنون اللغوية. وتصف كيف من أول الأمر استقصى معلمو المدرسة الابتدائية قبل الخدمة جوانب معرفة القراءة والكتابة البصرية وثمة انشغلوا في تعدودية النظم التقليدية والرقمية رداً على الأدب الواقعي التاريخي. ولقد قرأوا وتحللوا صوراً ووضعوا ردودهم على الشبكة العالمية كتابةً وبصريةً وخلقوا فسيفساء رمزية ومثلوا موقفاً ومسرحية دراما وحادثوا. وبعد ذلك اختاروا من هذه المصادر التمثيلية المتنوعة وأعادوا تصميمها كي يخلقوا كذا فيديو آي بود وعمقوا فيها مستكشفين جانباً من الكتاب. وقد تم تحليل ثلاثة مشاريع من المجموعة بحثاً عن الوسائل التي استغل فيها الطلاب الامتيازات المعينة من الطرق المتنوعة وقد تمت وصفة لاحتمالات التنفيذ في تعليم صفوف الابتدائية والاعدادية. 本文探讨一种可以通过数字技术促进语文教学的语境。文中描述小学教育的职前教师如何首先对视觉素养作多方面的研究，然后参与对历史性和非虚构性的写实文学的内容，以数字式及传统式的多模态形式作出回应的活动。他们一起阅读、解读图像、张帖线上文字和图解的回应、创作符号拼贴画、角色扮演、把戏剧化静态画面演活，和彼此交谈。接着，他们挑选和重新设计这些不同的表征资源，创制协作性网络电影，在电影中他们对该写实文学的某一方面作进一步的探讨。根据分组研习中的三个组别的资料，本文分析学生如何利用不同种类的模态所提供的特殊可用性。本文最后更说明这个研究对小学与中学课堂教学的含义。 Cet article explore un contexte dans lequel l'enseignement de la langue peut être amélioré grâce aux technologies numériques. Il décrit comment des enseignants d'école élémentaire en formation initiale ont examiné tout d'abord les aspects visuels de la lecture‐écriture, puis se sont engagés dans des formes multimodales de réponse numériques et traditionnelles avec une littérature classique non fictionnelle. Ils ont lu, interprété des images, collé en ligne des réponses écrites et visuelles, créé des collages symboliques, joué des rôles, fait de la mise en scène théâtrale, et débatti. Ils ont ensuite sélectionné puis redéfini ces diverses ressources de représentation pour créer des eFilms dans lesquels ils ont exploré davantage un aspect du livre. Trois de ces projets collectifs ont été analysés quant à la façon dont les étudiants ont capitalisé les possibilités qu'offrent ces différentes modalités. On décrit les implications pour l'enseignement élémentaire et le collège. В статье представлен один из возможных контекстов для развития языковых навыков с помощью цифровых технологий. Сначала будущие учителя начальной школы знакомились с некоторыми аспектами визуальной грамотности, а затем реагировали на историческую документальную литературу в цифровом и традиционном полимодальном формате. Они читали, интерпретировали изображения, отправляли письменные и визуальные ответы по электронной почте, создавали символические коллажи, разыгрывали сценки и целые спектакли и просто беседовали. Затем они выбирали из всех эти ресурсов то, что считали необходимым для создания совместных электронных фильмов, в которых они еще глубже исследовали тот или иной аспект книги. В статье проанализированы три групповых проекта с точки зрения наиболее оптимального выбора ресурсов из всего имеющегося арсенала. Описано значение полученных выводов для начальной и средней школы. Este artículo explora un contexto en el cual la instrucción de las disciplinas lingüísticas puede ser aumentado por medio del uso de tecnologías digitales. Describe cómo maestros de enseñanza primaria a nivel de preservicio primero investigaron aspectos de competencia visual, entonces respondieron a literatura histórica real usando tanto medios digitales como tradicionales. Leyeron, interpretaron imágenes, enviaron respuestas escritas y visuales en línea, crearon arte de colaje simbólico, asumieron diferentes papeles, ejecutaron escenografías dramáticas y conversaron. Luego seleccionaron y rediseñaron estos variados recursos figurativos para crear iPelículas (iMovies) en las que siguieron explorando un aspecto del libro. Tres de los proyectos en grupo se analizan para ver las maneras en que los alumnos se aprovecharon de lo que cada modalidad ofrecía en particular. Se describen las consecuencias para la instrucción en los salones de clase primaria e intermedia.